Titanic the definitive documentary collection. - Mill Creek Entertainment ([United States] : Mill Creek Entertainment, 2012)
The Titanic set sail from Southampton to New York City on April 10, 1912 on her maiden voyage. The hopes and lives of many were cut short when the Titanic collided with an iceberg five days later. But her story goes beyond the mere facts. The following four programs take the viewer deeper into the legend of the Titanic: Titanic Remembered; The Story of Captain Smith and the Titanic; Echoes of the Titanic; End of an Era; with a bonus documentary Titanic Survivors.
DISC 1. Titanic remembered ; The story of Captain Smith and the Titanic ; Echoes of the Titanic ; End of an era -- DISC 2. Titanic survivors.
Title from container.
Rating: TVG.
DVD, region 1.
109072
Keywords: Titanic (Steamship); Shipwrecks -- North Atlantic Ocean; Nonfiction films; Historical films; Documentary films